1997
DOI: 10.1172/jci119778
|View full text |Cite
|
Sign up to set email alerts
|

Immunological significance of cytotoxic T lymphocyte epitope variants in patients chronically infected by the hepatitis C virus.

Abstract: This study was performed to test the hypothesis that cytotoxic T lymphocyte (CTL) selection of hepatitis C virus (HCV) escape variants plays a role in HCV persistence. The peripheral blood CTL responsiveness of patients with wellestablished chronic hepatitis C to a panel of 10 prototype HCV peptides (genotype 1a) was compared with the corresponding sequences encoded by the infecting viruses in each patient. Variant viral peptide sequences were threefold more frequent in the presence of a CTL response than in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
252
1
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(265 citation statements)
references
References 44 publications
(50 reference statements)
8
252
1
4
Order By: Relevance
“…Identification of immunodominant epitopes and a more comprehensive study may resolve this question. However, the lack of evidence of immune escape in this study and the detection of the emergence of only one antagonist mutant in an earlier study 12 suggests that immune escape from CTL is not the major mechanism by which HCV ensures persistence in chronic infection.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Identification of immunodominant epitopes and a more comprehensive study may resolve this question. However, the lack of evidence of immune escape in this study and the detection of the emergence of only one antagonist mutant in an earlier study 12 suggests that immune escape from CTL is not the major mechanism by which HCV ensures persistence in chronic infection.…”
Section: Discussioncontrasting
confidence: 79%
“…The most attractive of these is ''immune escape'' whereby mutations arising within the HCV genome enable the virus to evade the host' s immune response. [7][8][9][10] Studies of HCV infection in chimpanzees have reported limited evidence of mutation within CD8 ϩ T cell epitopes associated with viral persistence, 11 but only limited studies have yet been reported in humans, 12 the results of which are equivocal.…”
mentioning
confidence: 99%
“…11,15 HCV can also escape CTL recognition by mutation of target epitopes, 3,39 an early event, which remains fixed thereafter, 6,40 and determines viral persistence. 41 Moreover, despite their ability to clear one HCV strain, patients may be reinfected with a heterologous strain that can then persist. 42 For these different reasons, it will be important to analyze the autologous HCV sequence in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-A2 and -B7 tetramers were produced as described in Altman et al 21 Peptides were [41][42][43][44][45][46][47][48][49] (GPRLGVRAT). HLA-A2 and HLA-B7-restricted pp65 CMV tetramers were used as controls.…”
Section: Patientsmentioning
confidence: 99%
“…Several studies indicate that HCV Class I restricted T-cell epitopes located within the NS3 protein are commonly recognized by liver-infiltrating and circulating cytotoxic T lymphocytes (CTL) of HCV-infected patients. [12][13][14][15][16][17] Briefly, total RNA was extracted from 140 L of serum or plasma specimens with the QiaAmp HCV-RNA column kit (Qiagen GmbH, Hilden, Germany) following the instructions from the manufacturer. Reverse transcription of viral RNA and primary PCR were performed in a single tube containing 5 L of RNA, 1 L of AMV-Expand HiFidelity enzyme mix (Roche Molecular Biochemicals, Mannheim, Germany), and 25 pmol of primers NS3-5 (5Ј-ACG TAC TCC ACC TAC GGC AA-3Ј; positions 4228 -4248) and NS3-6 (5Ј-AAG GTA GGG TCA AGG CTG AA-3Ј; positions 4745-4765).…”
Section: Hcv-rna Viral Load and Genotypingmentioning
confidence: 99%